Assistance and Capacity Building for Garut Sheep Farmers through the Implementation of the GrassApp Technology-Based Grass Supply Search System - Fawaz, Muhamad Fathur; Pamungkas, Bayu; Saputra, Dendi (Fakultas Kewirausahaan Universitas Garut, 2023)
The Garut sheep farming sector plays a crucial role in Indonesia's economy, especially in Garut Regency. However, farmers face challenges in ensuring a consistent and efficient grass supply for their livestock. The GrassApp, a technology-based grass supply search system, was developed to address these issues. This study aimed to evaluate the acceptance of GrassApp among Garut sheep farmers through a series of workshops and training sessions. The app, which uses GPS to locate grass supplies, is expected to improve feeding efficiency and productivity. Results indicate positive reception, with farmers acknowledging the app's benefits in saving time and resources. This study highlights the potential of technological innovations in enhancing agricultural practices, ultimately contributing to the sustainability of Garut sheep farming.